Carbohydrate restriction drives greater perturbations in circulating metabolites than low energy availability in elite male athletes - Dunlop, K. A.; Lawler, N. G.; Whitfield, J.; McKay, A. K. A.; Tee, N.; Ross, M. L.; Reinke, S. N.; Hawley, J. A.; Broadhurst, D.; Burke, L. M. (Physiological Reports, 2026)
Periods of low energy availability (LEA) are common in elite athletes and typically arise from reduced energy intake, often involving some degree of carbohydrate (CHO) restriction. Whether the metabolic profile created by energy restriction per se is distinct compared to that driven by CHO restriction is unknown. Using untargeted metabolomics, we examined metabolic perturbations linked to CHO restriction and energy restriction in plasma from elite male endurance athletes. In a semi-randomized controlled trial, athletes (n = 20) completed one of three 5-day dietary interventions: high energy-high CHO (HCHO); LEA (energy-restricted, CHO-reduced); or low-CHO, high-fat (LCHF; energy-matched, CHO-restricted). Plasma samples were taken at multiple timepoints pre- and post a standardized 25 km race walk protocol. Metabolomic analysis was performed using liquid chromatography-mass spectrometry (LC-MS), with multivariate analysis conducted using RM-ASCA+ and hierarchical clustering. A total of 5391 metabolic features were detected and 138 metabolites annotated. LCHF induced substantial metabolic perturbations, especially after prolonged exercise, including elevations in fatty acyls, hydroxy acids, dicarboxylic acids and acylcarnitine intermediates, responses not seen under LEA. We conclude that CHO restriction concomitant with a high-fat load induces a greater metabolic perturbation in selected lipid-based metabolites than short-term LEA exposure in elite athletes undergoing prolonged endurance exercise.